PERKEMBANGAN PENDIDIKAN KEWARGANEGARAAN (PKn) DI DALAM MEMBANGUN KARAKTER BANGSA PESERTA DIDIK - Pipit Widiatmaka (Fakultas Keguruan dan Ilmu Pendidikan Program Studi Pendidikan Pancasila dan Kewarganegaraan, 2022)
Indonesia has various kinds of problems, especially the character of the younger generation who are increasingly far from the values ​​of Pancasila. Civic education is the solution to the crisis of youth character in Indonesia because it is a study that develops three competencies, namely civic knowledge, civic disposition, and civic skills. The purpose of this study is to determine the development of civic education in building the character of the nation and the role of civic education in formal education. This study uses a qualitative approach by utilizing library research methods. The data collection technique with documentation and data analysis used is content data analysis. Since the founding of the Indonesian state, civics education from year to year has changed the material covered in it to be taught to students and always changes in the use of terms. Civic education can be provided in every educational path, from informal, and formal, to non-formal education, because civic education is the spearhead in instilling Pancasila values. Civic education can also be used as a vehicle for democratic education so that it can form citizens who have a democratic character based on Pancasila and UUD 1945. Through civic education, it is hoped that students will be able to master and apply the values ​​of Pancasila so that they can become good citizens.